THE ROLE OF INDONESIA'S ECONOMIC DIPLOMACY IN THE DYNAMICS OF INDONESIA'S RELATIONSHIP WITH AUSTRALIA UNDER THE LEADERSHIP OF JOKO WIDODO (2014-2016) - Della Junita Evasari (Sociae Polites, 2018)
This study discusses the relationship between Indonesia and Australia that have been unstable. Both countries make efforts to transform the various challenges and potential conflicts into an arena of cooperation that is beneficial to both countries, which realized through the implementation of economic diplomacy. Economic relations between Indonesia and Australia are important for both countries, but the value not maximized. As neighboring countries are close together, the cost is likely to be optimized, seeing from the data of strong economic performance and complementary both countries. The purpose of this study is to determine the role of Indonesian Economic Diplomacy in the dynamics of Indonesia's relationship with Australia in the era of President Joko Widodo's Government (2014-2016). This research uses a qualitative research methodology with a descriptive analysis approach. The theory used is the theory of diplomacy and the concept of economic diplomacy. The results show three roles of Indonesian economic diplomacy in the dynamics of Indonesia's relations with Australia in the era of President Joko Widodo. First, it seeks to increase cooperation between Indonesia and Australia in the economic sector (exports, imports, and investments), tourism, and education. Secondly, to improve the relationship between Indonesia and Australia to be closer and reduce the tension/conflict between the two countries. Third, encourage complementary relationships and win-win relationships. One of the implementations of Indonesia's economic diplomacy with Australia is the Indonesia-Australia Comprehensive Economic Partnership Agreement (IA- CEPA), which is currently in the process of negotiating both countries. Successful cooperation agreements will reflect strong ties between the two countries.